Alih Fungsi Pedestrian oleh Pedagang Kaki Lima di Jalan Gatot Subroto Medan Petisah - Sinurat, Riko Pan Demak; Saraswaty, Rina (Universitas Medan Area, 2025)
The rapid development of infrastructure in downtown Medan has led to the emergence of business, trade, and educational centres in various areas. As a metropolitan city, the City öf Medare serves as at centre of trade, offices, government, and industry. Public activities to reach such centres of activity can be carried out by motor transport or on foot. Good pedestrian facilities are essential for improving safety, comfort, as well as supporting an active lifestyle and a sustainable urban environment. However, many pedestrian lanes in the city of Medan, on Gatot Subroto Street, Central Petisah, have shifted their fumetians to other places of activity such as five-foot merchant kiosks and vehicle parking. The study aims to analyze the influence of five-foot merchants on the comfort of pedestrians in the use of pedestrian lanes on Gatot Subroto Street. The research method is carried out with a qualitative descriptive approach through field observations, questionnaires and in-depth interviews with road users and five-foot traders located from the Bukopin Bank Fountain Waterfront to the front of the Plaza Mall Field Fair.